(untitled) (Вісник: Міжнародні відносини, 2025)
Abstract. This article explores the potential of investments in the cryptocurrency segment, focusing on the factors driving this resurgence, the evolving landscape of decentralized finance (DeFi), and the long-term prospects for investors. Decentralized finance has emerged as one of the most promising sectors within the cryptocurrency ecosystem. By leveraging smart contracts and blockchain technology, DeFi platforms offer financial services without intermediaries, enabling users to lend, borrow, trade, and invest with unprecedented ease and transparency. The year 2023 marked a significant turning point for the cryptocurrency market, as it emerged from what many had dubbed the "cryptowinter." The cryptowinter of 2022 was triggered by a combination of macroeconomic challenges, including rising interest rates, inflationary pressures, and the collapse of major crypto entities like FTX. This period, characterized by declining asset prices, reduced investor sentiment, and widespread uncertainty, tested the resilience of both the industry and its participants. These events led to a loss of trust among retail and institutional investors alike. However, as the cryptowinter waned, new opportunities began to surface, revealing the untapped potential of investments in the cryptocurrency segment. Yet, as 2023 unfolded, the market demonstrated remarkable recovery capabilities. Despite market downturns, institutions continued to explore blockchain technology. In 2023, we witnessed greater participation from traditional financial players, such as banks and hedge funds, who recognized the transformative potential of cryptocurrencies and DeFi. Key words: investments in the cryptocurrency segment, landscape of decentralized finance, blockchain technology, market volatility, regulation, «cryptowinter», іnstitutional аdoption, yield opportunities, investment funds, Bitcoin, ETF Анотація. Мета статті полягає у визначенні потенціалу інвестицій у криптовалютний сегмент із детальним аналізом факторів, що впливають на його відродження, зміни ландшафту децентралізованих фінансів (DeFi) та довгострокові перспективи для інвесторів. Децентралізовані фінанси стали одним із найбільш перспективних секторів екосистеми криптовалют. За допомогою смарт-контрактів та технології блокчейн платформи DeFi надають фінансові послуги без посередників, дозволяючи користувачам надавати кошти у борг, отримувати кредити, торгувати та інвестувати з таким рівнем зручності та прозорості, які були недоступними у минулому. Рік 2023 став значною точкою зміни для ринку криптовалют, оскільки він вийшов із того періоду, який отримав назву "криптозима". Криптозима 2022 року була викликана комбінацією макроекономічних викликів, включаючи підвищення ставок за кредитами, інфляційний тиск та колапс великих криптоструктур, таких як FTX і Terra. Цей період, що характеризувався падінням цін на активи, зменшенням інвестиційних намірів та загальною невизначеністю, перевірив на стійкість як саму галузь, так і її учасників. Ці події призвели до втрати довіри як з боку роздрібних, так і інституціональних інвесторів. Проте, коли криптозима почала затухати, почали з’являтися нові можливості, які відкрили не використаний потенціал інвестицій у сегмент криптовалют. По мірі розвитку подій у 2023 році, ринок продемонстрував вражаючу здібність до відновлення. Попри ринковий спад установи продовжили своє вивчення технологій блокчейну. Рівень інституціонального сприйняття суттєво зріс, коли у 2023 році стала очевидною значна участь великих традиційних фінансових гравців, серед яких, в першу чергу, слід виділити банківські установи та хедж-фонди, що визнали трансформаційний потенціал криптовалют і децентралізованих фінансів (DeFi).